ISLAM NORMATIF DAN ISLAM HISTORIS - Kusmiran; Amril M (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2023)
This paper discusses the relationship between normative Islam and historical Islam. The method used is library research. The results of the study show that: 1) the notion of normative Islam is: norms, teachings, references, provisions regarding good and bad issues, what may be done and what may not be done while historical Islam means history which means past experience of mankind, 2) Normative Islamic studies explain law/fiqh, theology, philosophy and Sufism, 3) historical Islamic studies give birth to traditions or empirical study disciplines: religious anthropology, sociology of religion, psychology of religion, 4) the relationship between normative Islam and historical Islam can form a dialectical relationship and tension. Dialectical relations occur when there is a back-and-forth dialogue that illuminates each other between text and context